Deadenylation by the CCR4‐NOT complex contributes to the turnover of hairy‐related mRNAs in the zebrafish segmentation clock. Issue 20 (15th October 2018) - Fujino, Yuuri; Yamada, Kazuya; Sugaya, Chihiro; Ooka, Yuko; Ovara, Hiroki; Ban, Hiroyuki; Akama, Kagari; Otosaka, Shiori; Kinoshita, Hirofumi; Yamasu, Kyo; Mishima, Yuichiro; Kawamura, Akinori
Abstract : In the zebrafish segmentation clock, hairy/enhancer of split ‐related genes her1, her7, and hes6 encodes components of core oscillators. Since the expression of cyclic genes proceeds rapidly in the presomitic mesoderm (PSM), these hairy ‐related mRNAs are subject to strict post‐transcriptional regulation. In this study, we demonstrate that inhibition of the CCR4‐NOT deadenylase complex lengthens poly(A) tails of hairy ‐related mRNAs and increases the amount of these mRNAs, which is accompanied by defective somite segmentation. In transgenic embryos, we show that EGFP mRNAs with 3′UTRs of hairy ‐related genes exhibit turnover similar to endogenous mRNAs. Our results suggest that turnover rates of her1, her7, and hes6 mRNAs are differently regulated by the CCR4‐NOT deadenylase complex possibly through their 3′UTRs in the zebrafish PSM. Abstract :